GRANULOMETRIC ANALYSIS OF PALEOTSUNAMI DEPOSITS CANDIDATE IN TERNATE ISLAND, NORTH MALUKU - ⠀ Yudhicara (Marine Geological Institute of Indonesia, 2023)
Ternate Island is a volcanic island located in the Maluku Sea. Tsunami ever hit Ternate before 1900 or occurred before the age of the people living in this island. The paleotsunami suspect have been found in the western coast of Ternate Island. The outcrop has 50 m length and 1 m width, was discovered beneath the Gamalama eruption product which occurred in 1907. The paleotsunami candidate consists of at least five layers originating from different tsunami events. The granulometric analysis was carried out for each layer. The results obtained were that paleotsunami sediments had poorly sorted which indicated that the grain sizes were mixed, this was due to the energy of tsunami wave varied in time when transporting and depositing the sediments. Skewness varies from very fine to very coarse, indicating a change in the energy of the tsunami wave that occurs from very high when rising inland to decreasing as it returns to sea. Kurtosis varies from leptokurtic, platykurtic, and mesokurtic. Variations in mean, sorting, skewness and kurtosis values indicate a change in tsunami wave energy which causes a change in grain size. The granulometric analysis shows that the deposition of the youngest paleotsunami deposits candidate was initiated by a very strong current with the greatest energy, thus depositing very coarse sand to gravel, followed by a gradual decrease in energy and the tsunami wave process began to reverse towards the sea, then receded with the lowest energy and deposited finer grains. The sediment sources come from two different places, this shows that the sources come from the sea and the coast around the deposited paleotsunami candidates.